PETROLOGY AND GEOTECTONIC SIGNIFICANCE OF PLAGIOGRANITE FROM THE SARIKARAMAN OPHIOLITE (CENTRAL ANATOLIA, TURKEY) - Yaliniz, M. Kenan; Floyd, Peter A.; Göncüoğlu, M. Cemal (Ofioliti, 2000)
Plagiogranites within the supra-subduction zone (SSZ) type Sarikaraman Ophiolite (SO), Central Anatolia, are very fine to coarse grained leucocratic rocks with a range of occurrences as simple narrow fracture infilling to wide complex zones of net-veining or agmatites with numerous, partly assimilated enclaves of gabbro and dolerite. Petrographically, they are characterized by the textures ranging from hypidiomorphic granular to granophyric intergrowths of quartz and plagioclase. Geochemically, major and trace elements data revealed that the plagiogranites belong to the typically low-potassium series of ophiolitic complexes and show similar geochemical characteristics with the Ocean-Ridge Granites. They are characterized by 10-20 times enriched flat chondrite REE patterns with a negative Eu anomalies relative to mafic component in the SO. This confirms the cogenetic nature of the plagiogranites and indicates progressive fractionation in the Sarikaraman mafic magma. Field observations coupled with major-element and trace element chemistry support to a model by which the plagiogranites of SO could be formed as a fractional crystallization of Sarikaraman basaltic magma in SSZ setting, like the other eastern Mediterranean ophiolitic plagiogranites such as Troodos, Pindos, and Oman.